Seasonal variation of biotic and abiotic parameters in parallel neotropical fishponds - Sipaúba-Tavares, L. H.; Seto, L. M.; Millan, R. N. (Instituto Internacional de Ecologia, 2014)
The present study was carried out to evaluate the phytoplankton community and water quality in four parallel fishponds (FP1 to FP4) during one year. Some abiotic parameters of water column and phytoplankton was sampled in four sites, one in each fishpond. Similarity analysis showed that FP2 fishpond was markedly different for the others ponds with regard to phytoplankton community. Conductivity, orthophosphate, temperature, TSS and hardness parameters were significantly different (p<0.05) between fishponds and all limnological parameters were significantly different (p<0.01) among period (months). Organic matter and phosphorus of the sediment were significantly different (p<0.01) only among fishponds. In current study Chlorophyceae and Bacillariophyceae occurred in most months. Cyanobacteria density in April and May was higher in all fishponds, at FP3 represented 71.4% in April and FP1 represented 78.7% in May of total reported, with chlorophyll-a content lower than 41 mg.L−1. The physical and chemical parameters of fishponds water constituted relations between the parameters and algae occurrence. The present study however, indicated that Cyanobacteria was more frequent in the fishponds after the fish grow-out period (April), and the water quality should be monitored more frequently in this period, due to the high total phosphorus, orthophosphate and chlorophyll-a contents.

O presente estudo avaliou durante um ano a comunidade fitoplanctônica e os fatores abióticos da água de quarto tanques de piscicultura (FP1 ao FP4) com disposição paralela. Alguns fatores abióticos da água e do fitoplâncton foram amostrados em quarto pontos, localizados um em cada tanque de piscicultura. Análise de similaridade mostrou que o tanque de piscicultura FP2 foi diferente dos outros tanques em relação a comunidade fitoplanctônica. Condutividade, ortofosfato, temperatura, STS e dureza foram diferentes (p<0,05) entre tanques e todas as variáveis limnológicas variaram entre o período de estudo (p<0,01). Matéria orgânica e fósforo do sedimento variaram (p<0,01) somente entre os tanques. Chlorophyceae e Bacillariophycea estiveram presentes em todos os meses amostrados. Em abril e maio foi observada elevada densidade de Cyanobacteria em todos os tanques sendo que no FP3 representou 71,4% em abril e no FP1 78,7% em maio do total encontrado, com teor de clorofila-a abaixo de 41 mg.L−1. Os parâmetros físico-químicos da água dos tanques de piscicultura apresentaram relação com a ocorrência do fitoplâncton nestes sistemas. Os resultados deste estudo indicaram a maior frequência de Cyanobacteria no período após a engorda de peixes (abril) necessitando maior monitoramento da qualidade da água devido aos altos teores de fósforo total, ortofosfato e clorofila-a observados neste mês (abril)
Variação sazonal dos parâmetros bióticos e abióticos em tanques de piscicultura com disposição paralela de região neotropical
Keywords: Algae; Aquaculture; Physical and chemical parameters; Water quality; Alga; Aquicultura; Variáveis físicas e químicas; Qualidade da água